Annual Report on Exchange Arrangements and Exchange Restrictions 1960. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1960)
This paper focuses on progress in reducing or eliminating exchange restrictions that has been substantial and has been made on a wide front; retrogressions have been comparatively few. The beneficial effects of the widening scope of currency convertibility have been felt in many areas, and the evolution toward freer, more orderly, and less discriminatory trade and payments has been strongly supported by a high level of economic activity, expanding international trade, and the general maintenance of monetary stability. Recent developments in trade and payments have not merely reduced the scope of restrictions; they have also changed the nature of these restrictions. Of key importance was the introduction of external convertibility by several countries at the end of 1958. Quotations for externally convertible currencies in exchange markets throughout the world have shown only minor fluctuations in the past twelve months. Most Western European currencies have generally been strong in terms of the US dollar.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet